2020
DOI: 10.4103/ijmr.ijmr_1676_18
|View full text |Cite
|
Sign up to set email alerts
|

Potential of neutrophil to lymphocyte ratio in predicting sustained remission in rheumatoid arthritis compared to other immune activation markers

Abstract: Background & objectives : Cells and cell proportions may indicate the equilibrium status of the immune system. The present study was conducted to evaluate the role of cytokines and the immunocompetent cells as biomarkers of remission in rheumatoid arthritis (RA) patients intended to withdraw or reduce disease-modifying anti-rheumatic drug (DMARD) treatment. Methods : This prospective observational study involved newly diagnosed and treated RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…We also obtained some immune cell related to RA synovial lesions. Compared with other immune activation markers, neutrophils are at the center of RA pathology (31) The ratio of neutrophils to lymphocytes has great potential in predicting sustained remission of RA (32). Plasmacytoid dendritic cells participate in the local in ammatory environment of RA (33).…”
Section: Discussionmentioning
confidence: 99%
“…We also obtained some immune cell related to RA synovial lesions. Compared with other immune activation markers, neutrophils are at the center of RA pathology (31) The ratio of neutrophils to lymphocytes has great potential in predicting sustained remission of RA (32). Plasmacytoid dendritic cells participate in the local in ammatory environment of RA (33).…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported NLR values, whereas 11 also reported PLR values (Table 1). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] There was no disagreement between the two investigators.…”
Section: Systematic Researchmentioning
confidence: 99%
“…Eighteen studies investigated the NLR in 2122 RA patients with active disease (mean age 50 years, 20% males) and 1071 RA patients in remission (mean age 50 years, 25% males). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Five studies were conducted in China, 29,31,33,40,41 four in Turkey, [26][27][28]34 four in India, 25,30,35,36 two in Egypt, 32,42 and one in the Philippines, 37 Poland 38 and Thailand, 39 respectively. Eight studies were prospective, 25,27,29,30,35,36,38,42 whereas the remaining 10 were retrospective.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 It must be emphasized, however, that increased systemic inflammation is not pathognomonic solely for malignancies. Increased SIR is predominately observed in autoimmune diseases including rheumatoid arthritis, [32][33][34] spondyloarthropathies, 35,36 Crohn's disease, 37 diabetes, 38 and Hashimoto's thyroiditis 39 and has even been reported in patients with COVID-19. 40 Furthermore, multiple demographic and lifestyle factors, including sex, age, race, marital status, body mass index, physical activity, smoking history, and alcohol consumption are independently associated with inflammatory biomarkers; these should be also taken in consideration to more accurately assess their prognostic power.…”
Section: Introductionmentioning
confidence: 99%